2020
DOI: 10.20944/preprints202010.0417.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust Design of a Future 100% Renewable European Energy Supply System with Hydrogen Infrastructure

Abstract: In light of the latest trends in global installed capacities, the importance of variable renewable energy sources (VRES) to future energy supply systems is evident. Despite this, the inherent intermittency of VRES remains an obstacle to their widespread adoption. Green hydrogen is often suggested as an energy carrier that can account for this in a sustainable manner. In the analysis, a robust European energy system in the context of 2050 and with 100% VRES energy supply is designed through an iterative minimal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The energy system definition employed here is the same as in the work of Caglayan et al 2021 [44], where it is explained in detail; therefore, a brief description of their energy system concept is presented here. For the regional boundaries of Europe, 96 regions were considered in accordance with the e-Highway project [45].…”
Section: System Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy system definition employed here is the same as in the work of Caglayan et al 2021 [44], where it is explained in detail; therefore, a brief description of their energy system concept is presented here. For the regional boundaries of Europe, 96 regions were considered in accordance with the e-Highway project [45].…”
Section: System Definitionmentioning
confidence: 99%
“…For the regional boundaries of Europe, 96 regions were considered in accordance with the e-Highway project [45]. In each region, energy carriers can be generated, consumed, converted or stored using the same technologies as proposed in Caglayan et al 2021 [44], as is shown in Fig. 1.…”
Section: System Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technologies' annual operational costs (OPEX), as percentages of the PV CAPEX, and economic service lives were kept the same as the ones suggested by the corresponding costing methodology. The weighted average cost of capital (WACC) was fixed at 8% for all technologies to maintain consistency with similar assessments [24,32,42,57]. Regional differences in technology costs and access were not considered in the costing procedure.…”
Section: Techno-economic Parametersmentioning
confidence: 99%
“…The quest of finding a lasting solution to pollution-free clean air environment has led to the formulation of various policies and agreements like the Kyoto Protocol and Paris Agreement by all stake holders across the globe [1], [2]. Due to technological advancement in most developed countries, the demand for energy to sustain these buoyant economies such as extraction of gas hydrogen and liquid hydrogen from wind power and their techno-economic analysis, offshore oil and gas exploration has seen an upward trajectory in the last few decades [3]- [5]. Unlike developing countries, these giant economies have exploited various medium of energy generation to meet their demand during peak hours.…”
Section: Introductionmentioning
confidence: 99%